Refinements and Generalizations of Functional Dresher’s and Bellman’s Inequalities - Rabia Bibi; Muhammad Shahzad (Abstract and Applied Analysis)
We give refinements and generalizations of the Dresher and Bellman inequalities for positive linear functionals. We also give reverse of the new obtained generalized version of these inequalities. Finally, we apply our results on time scales integrals to obtain refinements and generalizations of time scales Dresher’s and Bellman’s inequalities.